TRACE ELEMENTS IN DIAMOND INCLUSIONS FROM ECLOGITES REVEAL LINK TO ARCHEAN GRANITES - Ireland T.R.; Rudnick R.L.; Spetsius Z. (My University, 1994)
We report trace element data for rare garnet and clinopyroxene inclusions trapped within diamonds occurring in eclogite xenoliths from the Siberian craton. These inclusions are more depleted in incompatible trace elements and have lower Mg# than the eclogite host minerals, reflecting metasomatic enrichment of the eclogites after diamond formation by high Mg# melts that are enriched in incompatible trace elements (such as kimberlites). A reconstructed whole rock composition (using inclusion data) is severely depleted in light rare earth elements and niobium but shows a marked strontium enrichment. The melt in equilibrium with this eclogite is calculated to have had very high and and is Nb depleted (if rutile is present), characteristics similar to those of some convergent margin magmas but most especially Archean tonalitic rocks. Experimental petrologic studies demonstrate that eclogites of the type described here are in equilibrium with silicic melts such as tonalites or trondhjemites. Thus, both our trace element data and petrological considerations are consistent with the eclogites forming in equilibrium with Archean tonalitic or trondhjemitic magmas. Our data may therefore comprise the first evidence for the fate of these voluminous residues. A corollary of our findings is that trace element and isotopic data from eclogite minerals must be interpreted with caution because of the eclogite's complex evolutionary history. Specifically, models of early Earth differentiation based on isotopic data from Siberian eclogites [1,2] require re-evaluation.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей